2003
DOI: 10.1111/1468-2389.00228
|View full text |Cite
|
Sign up to set email alerts
|

Using Recruiter Assessments of Applicants’ Resume Content to Predict Applicant Mental Ability and Big Five Personality Dimensions

Abstract: Information provided on applicants' resumes provides a convenient, cost-effective means for applicant screening. We sought to determine if recruiters' assessments of the presence of certain types of information on job applicants' resumes was related to applicants' general mental ability and personality traits. Forty recruiters from 35 organizations assessed the extent to which specified items were present on the resumes of job applicants. Results indicated relationships between recruiters' judgments regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 53 publications
(54 reference statements)
6
76
1
1
Order By: Relevance
“…In summary, previous research has found recruiters are able to make reliable assessments regarding the presence of resume content (Cable and Gilovich 1998;Cole et al 2003a) and applicant attributes when screening applicant resumes (Brown and Campion 1994). Research findings from a number of studies, both experimental and fieldbased, also suggest that recruiters form impressions of applicants' subjective attributes based on resume content (Cable and Gilovich 1998), and, more importantly, they use these inferences when evaluating applicants' employability (Brown and Campion 1994;Cole et al 2004).…”
Section: Previous Research On Resume Screeningmentioning
confidence: 87%
See 2 more Smart Citations
“…In summary, previous research has found recruiters are able to make reliable assessments regarding the presence of resume content (Cable and Gilovich 1998;Cole et al 2003a) and applicant attributes when screening applicant resumes (Brown and Campion 1994). Research findings from a number of studies, both experimental and fieldbased, also suggest that recruiters form impressions of applicants' subjective attributes based on resume content (Cable and Gilovich 1998), and, more importantly, they use these inferences when evaluating applicants' employability (Brown and Campion 1994;Cole et al 2004).…”
Section: Previous Research On Resume Screeningmentioning
confidence: 87%
“…Furthermore, a number of resume biodata items were related with recruiters' evaluations of applicants' subjective and objective attributes. Thus, when recruiters use applicants' resumes as the initial screening tool, there is an implied assumption that information reported on the resume is linked to job relevant attributions, including personality characteristics (Ash et al 1989;Cole et al 2003a;Rubin et al 2002), which are important for job success.…”
Section: Previous Research On Resume Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…While resumes and applications provide much factual and verifiable information such as educational achievements, certifications, licenses, experience, and so on, employers also use them to infer other characteristics such as personality, intelligence, leadership, and work ethic (Cable & Gilovich, 1998;Cole, Feild, Giles, & Harris, 2009). They then use these inferences to assess prospect employability (Brown & Campion, 1994;Cole, Feild, & Giles, 2003;Cole, Rubin, Feild, & Giles, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Extracurricular activities are an important part of an student's vita (e.g., Rubin et al 2002) and are usually presented on the résumé. Several psychological studies show that recruiters' initial perceptions of an applicant's skills and personality indeed depend on her extracurricular activities (e.g., Nemanick and Clark 2002, Cole et al 2003, Tsai et al 2011). Nemanick and Clark (2002), Chia (2005) and Cole et al (2007) present evidence that résumés with more extracurricular activities receive more invitations to job interviews and job offers.…”
Section: Resultsmentioning
confidence: 99%